Model Spasial Kesesuaian Habitat dari Macaca Nigra - Yohana Maria Indrawati; Dones Rinaldi; Lilik Budi Prasetyo (Department of Forest Resources Conservation and Ecotourism - IPB University, 2013)
The remaining habitat of Black Crested Macaques in Sulawesi is limited only in conservation areas, and therefore it is an urgent need to map its habitat suitability model. This work can be achieved by application of Geographic Information System (GIS). Data observation was conducted in Tangkoko Nature Reserve and Batuputih Nature Recreation Park from July to September 2009. The model was then extrapolated to Tangkoko Nature Reserve, Duasudara Nature Reserve, Batuputih Natural Recreation Park, and Batuangus Nature Recreation Park. Modelling of Black Crested Macaque’s habitat was conducted by spatial identification of their encounter points toward habitat and disturbance factors. Habitat suitability model of Black Crested Macaque was Y = (2.399xFcroad) + (2.399xFcriver) + (2.399xFcNDVI) + (2.399xFcelevation) + (1.142 xFcbuilding) + (0.957xFcslope). Cumulative score was divided into threeclasses namely high suitability habitat, medium suitability habitat, and low suitability habitat. Tangkoko Nature Reserve has highest rate of high suitability habitat whereas Duasudara Nature Reserve has lowest rate of high suitability habitat. Tangkoko Nature Reserve forms the best suitable habitat for Black Crested Macaque whereas both Duasudara Nature Reserve and Batuangus Nature Recreation Park are the least suitable habitat for species. Keywords: model, habitat, Black Crested Macaque.